Prenatal corticosterone altered glucocorticoid receptor and glucocorticoid metabolic enzyme gene expression in chicken ovary - Abdelkareem A. Ahmed (Asian Pacific Journal of Reproduction, 2016)
Objective: The acute stress response is an adaptive physiological mechanism which allows an organism to respond and survive deleterious stimuli in the surrounding environment. In mammals, prenatal glucocorticoids exposure (GCs) reprograms offspring phenotype and reproductive performance. In the present study, we investigated potential prenatal GC exposure on the glucocorticoid receptor (GR), mineralocorticoid receptor (MR) and GC metabolic genes mRNA expression in the ovary of chickens. Methods: We injected low (0.2 μg) and high (1.0 μg) doses of corticosterone (CORT) in ovo before incubation and measured the changes in GCs metabolic enzymes genes in ovarian follicles 1 (F1), F2 and F3 post hatching. Results: The high dose CORT treatment significantly (P < 0.0) decreased 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1) mRNA expression in F1, F2, F3 and in the ovary compared to the control and low groups. However, the high dose CORT treatment significantly (P < 0.0) increased 11β-hydroxysteroid dehydrogenase type 2 (11β-HSD2) mRNA expressions in F1, F2, F3 and in the ovary compared to control and low groups. Likewise, in ovo injection of high dose CORT significantly (P < 0.0) decreased 20-hydroxysteroid dehydrogenase (20-HSD) mRNA expression in F2, F3 and ovary compared to the control and low groups. Moreover, CORT treatment reduced GR mRNA expression in F1, F2 and F3 but not ovary. CORT treatment decreased MR mRNA only in F2. Conclusions: Prenatal CORT exposure modified GR, MR and GC metabolic enzymes gene expression in ovarian follicles, thus it may reprogram reproductive function.